PENGARUH CURRENT RATIO DAN RETURN ON ASSET TERHADAP PERTUMBUHAN LABA PADA SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - FARIDA SAGALA (LP2MTBM MAKARIOZ, 2021)
This study aims to determine and analyze the effect of Current Ratio and Return On Assets to Earnings Growth inTransportation Sub Sector Companies listed on the Indonesia Stock Exchange. The Sample selection using purposivesampling from 35 companies registered by the company only 10 samples. The independent variables studied were financialratios consisting of Current Ratio (CR) and Return On Assets (ROA) while the dependent variable was Earning Growth. Theresults of this study indicate that Current Ratio and Return On Assets have a negative but not significant effect on earningsgrowth. The results of simultaneous hypothesis testing (F test) showed that Current Ratio and Return On Assets did notaffect earnings growth. Based on the Determination Coefficient test results obtained 0.32 or 3.2% which means that thevariable Current Ratio, and Return On Assets can explain Earnings Growth of 3.2%, while the remaining 96.8% explained byother variables not examined in this study.